Comparison of Orchard-grass and Sweet Maize for Doubled Haploid Plant Production via Wide Hybridization in Bread Wheat - Avcı, Süleyman; Kutlu, İmren (Turkish Journal of Agriculture - Food Science and Technology, 2020)
In this study, the potential of haploid regeneration was investigated in hybridization of six bread wheat F1 hybrids known response to another culture with orchard-grass (Dactylis glomerata L.) and sweet maize varieties (Baron, Challenger and Merit). A total of 150 wheat spikes were pollinated with orchard grass and sweet maize and 2730 pseudo-seeds were produced. Although the high rate of developed pseudo-seeds was developed from bread wheat F1 hybrids × orchard-grass, no embryos were produced. Developed pseudo-seeds (2057 number) of bread wheat × sweet maize produced 53 haploid embryos and only 8 of them were regenerated. Developed green plantlets were vernalized and applied colchicine and only four of them produced fertile seeds. The highest rate (5.9) of haploid embryo formation within wheat genotypes was determined in DH20 × Kate A-1. Although the highest haploid embryo formation was observed in Challenger with 3.5% among sweet maize genotypes, it had no effect on plant regeneration. Also, the mixture of pollen of sweet maize varieties increased haploid plant regeneration. It has been observed that some F1 hybrids such as DH20 × Kate A-1 and DH6 × Altay 2000 with low anther response gave better results in terms of haploid embryo formation and regeneration. The means of fertile spike percentages and number of seeds per fertile spike were 26.75% and 9.83, respectively in developed green plants. As a result, bread wheat × sweet maize hybridization will be a good alternative to obtain a homozygous line in a short time in bread wheat genotypes with low anther response.